2018
DOI: 10.4012/dmj.2017-065
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical properties and resorption progress of porcine skin-derived collagen membranes: <i>In vitro</i> and <i>in vivo</i> analysis

Abstract: The aim of the present study was to evaluate the physiochemical properties and resorption progress of two cross-linked, porcine skin-derived collagen membranes and compare their features with those of a membrane without cross-linking (Bio-Gide ® [BG], Geistlich Biomaterials, Wolhusen, Switzerland). Three porcine skin-derived collagen membranes, dehydrothermally (DHT) crosslinked (experimental), DHT and 1-ethyl-3(3-dimethylaminopropyl)-carbodiimide (DHT/EDC) cross-linked (experimental) and BG were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…(2) Enzyme resistance test: Samples were immersed in a 0.13% porcine trypsin solution (Sigma-Aldrich, St. Louis, MO, USA), and incubated at 37 °C [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Enzyme resistance test: Samples were immersed in a 0.13% porcine trypsin solution (Sigma-Aldrich, St. Louis, MO, USA), and incubated at 37 °C [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The source of the collagen varies, but it is typically obtained from bovine tendon, bovine dermis, calf skin or porcine dermis [ 12 ]. Porcine skin-derived collagen membranes are widely used in GBR procedures because porcine dermis primarily consists of type I collagen and its 3D architecture is similar to that of native extracellular matrix [ 13 ]. Purified bovine and porcine collagen derived from tendons, dermis (skin), pericardium and other regions has also been shown to be suitable as donor material [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results indicated that in the case of trypsin-treated collagen fibers (over 72 h), the collagen fibrils still kept their structural integrity by retaining their triple-helical conformation [43]. Yin-Zhe et al [42] previously reported that higher collagen density and compact structure may be a reason of slower biodegradation. However, further studies are required in order to assess whether the results obtained in our study can be applied to humans, as the local environment in the oral cavity is a complex biochemical "reactor" difficult to mimic.…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed for the native membranes can be explained by the cross-linking techniques used by the manufacturers, as any cross-linking technique may have uncertain effects on the structure of collagen membrane [42].…”
Section: Discussionmentioning
confidence: 99%